Giuseppe la Bua: Cicero and Roman Education. Reflections on Rhetorical Topics and Ciceronian Scholarship (Global Journal of Human-Social Science, 2021)
Ciceronian scholars preserve rhetorical models. Orator studies how speak well and how impact on the history of his State. Cicero and Roman education: the reception of the speeches and ancient
Keywords: ciceronian scholarship; giuseppe la bua; edition of cicero's speeches; ethics and politics; teaching cicero's oratory